2011
DOI: 10.1007/s00464-011-2066-6
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of peritoneal fluid contamination following transabdominal vs. transanal specimen extraction in laparoscopic left-sided colorectal resections

Abstract: Although a higher peritoneal contamination was found in the NOSE procedures, there were no significant differences in clinical outcomes relative to standard approach. Avoiding a minilaparotomy to extract the specimen resulted in a significantly lower postoperative analgesic requirement in the NOSE group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 13 publications
2
89
0
1
Order By: Relevance
“…In addition, Senagnore et al [41] showed that patients with a higher BMI were associated with a higher conversion rate to open surgery, longer operation time, higher prevalence of complications, and higher prevalence of anastomotic leakage in laparoscopic colectomy. Due to the effects of the BMI, two included studies [16,26] took BMI ≤30 kg/m 2 and one included study [28] took BMI ≤28 kg/m 2 as inclusion criteria for transanal specimen extraction. Based on the consensus mentioned above, strict and thorough criteria for patient selection for NOSE are expected in the future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, Senagnore et al [41] showed that patients with a higher BMI were associated with a higher conversion rate to open surgery, longer operation time, higher prevalence of complications, and higher prevalence of anastomotic leakage in laparoscopic colectomy. Due to the effects of the BMI, two included studies [16,26] took BMI ≤30 kg/m 2 and one included study [28] took BMI ≤28 kg/m 2 as inclusion criteria for transanal specimen extraction. Based on the consensus mentioned above, strict and thorough criteria for patient selection for NOSE are expected in the future.…”
Section: Discussionmentioning
confidence: 99%
“…After reading titles and abstracts, 21 studies were shown to be pertinent. Finally, nine studies [16,[22][23][24][25][26][27][28][29] were found to fit the inclusion criteria after reading the full text (Fig. 1).…”
Section: Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A prospective study of peritoneal fl uid contamination following laparoscopic leftsided resections with and without NOSE demonstrated positive peritoneal cultures in 100 % and 89 % of patients, respectively. Only one of 17 patients in the NOSE group developed an anastomotic leak, and there was no difference in infectious complications between the two groups [ 10 ].…”
Section: Natural Orifi Ce Specimen Extraction (Nose)mentioning
confidence: 80%